0353 Altered Modulation Of Spindle Density Across The Night In Older Adults With Chronic Insomnia. (12th April 2019) - Grimaldi, Daniela; Papalambros, Nelly; Malkani, Roneil G; Reid, Kathryn J; Abbott, Sabra M; Zee, Phyllis C
Abstract: Introduction: Sleep spindles serve critical functions for sleep promotion and maintenance by potentially gating sensory information to the cortex. A reduction in spindle density has been described in young-middle age adults with chronic insomnia suggesting a role in sleep quality. Aging is associated with increased prevalence of insomnia and concomitant reduction in spindle density and duration, yet the nature of spindle characteristics in older insomniacs remains largely unexplored. The aim of this study was to characterize spindles features and their distribution across the cycles of sleep in older adults with insomnia and good sleepers of similar age. Methods: Preliminary data were obtained from 17 adults with chronic insomnia (INS: 66±8 years, 14 females) and 8 good sleeper controls (CN: 68±9 years, 8 females). Participants completed four consecutive nights of polysomnography during which they were given 8 hours of sleep opportunity based on habitual sleep time. Spindles (11-15Hz) were detected automatically during sleep stages N2 and N3 on night 4 from the left central EEG channel. Duration, amplitude, frequency and spindle density (number/min) were calculated. Spindle density distribution across four cycles of sleep was also assessed. Results: Sleep macrostructure was similar in INS and CN. During N2, spindle density was reduced in INS compared to CN (3.8±2.2 and 5.8±1.8, respectively; p= 0.029) while spindle duration was increased (937±79 ms, 860±81 ms, respectively; p=0.009). During N3, spindle features were similar in INS and CN. There was also a reduction in spindle density across the cycles of sleep (group effect p= 0.033) during N2, particularly evident during cycle 1 (p= 0.03) and 2 (p= 0.01) for the insomnia group compared to controls. No significant differences were observed in spindle density across the cycles of sleep in N3. Conclusion: Differences in spindle features and temporal distribution across the night may represent a neurophysiological marker of altered sleep micro-structure in older adults with insomnia. Support (If Any): P01 AG11412